A atividade aula de teatro como instrumento na produção de conhecimento - Oliveira, Dionéia Menin da Silva (2011)
This research aims to understand with critical mind, within the social-historical cultural perspective, the social activity of the drama class, in order to verify how the roles of the teacher-director and the learners-actors contribute to the character s elaboration, searching for the transformation of all the participants. It is understood that the creation of a collaborative space can lead students of drama class of the school musical into situations to show and contrast senses to elaborate the characters. This study is shown as a critical research of collaboration, as it searches for the participants transformation and focus on language. It belongs to the Applied Linguistics studies and has its principals based on the Social-Historical Cultural Theory proposed by Leontiev, Engestron and Liberali. This project analyzes the organization of the social activity of drama, with emphasis on the language role as a mediator of the relationships established by the individuals. It is considered that the argumentation allows the interlocutors to show their senses in search for the elaboration of shared meanings. From Vygotsky, Newman and Holzman on, the concepts of meaning and sense, and the zone of proximal development are being used. The analysis of the data focus on the argumentative potential of the interactions and it is based on the categories proposed by Perelman and Olbrechts- Tyteca, Charaudeau and Pontecorvo. The analysis shows that the students enhance their argumentation when they are challenged, changing the drama class into a space of collaboration among them. In this process, the performance, based on Stanislavsky and Vigotsky, enables the students to visualize the character s personification, using their own lives resources and their emotional memories to build new shared meanings